2023
DOI: 10.1038/s41598-023-28724-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of anti-Müllerian hormone influence pregnancy outcomes associated with gonadotropin-releasing hormone antagonist treatment: a retrospective cohort study

Abstract: As a specific predictor of ovarian reserve, serum anti-Müllerian hormone (AMH) has become an area of intense research interest in the field of assisted reproductive technology. We assessed the relationship between AMH levels and pregnancy outcomes in Chinese patients and investigate the influencing factors of cumulative live birth in patients with high AMH levels. A total of 1379 patients starting their IVF/ICSI cycle were divided into normal (Group A, 1.1–4.0 ng/ml, n = 639) and high (Group B, > 4.0 ng/ml,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Several studies have explored the relationship between baseline serum AMH levels and pregnancy outcomes following IVF treatment ( Liu et al, 2022 ; Hou et al, 2023 ; Li et al, 2023 ; Yuwen et al, 2023 ). In women with PCOS results have been inconsistent with some authors reporting higher AMH levels to be associated with better reproductive outcomes ( Xi et al, 2012 ; Tal et al, 2015 ), while others found the opposite ( Xi et al, 2012 ; Tal et al, 2020 ; Guo et al, 2021 ; Sun et al, 2021 ; Vale-Fernandes et al, 2023a ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the relationship between baseline serum AMH levels and pregnancy outcomes following IVF treatment ( Liu et al, 2022 ; Hou et al, 2023 ; Li et al, 2023 ; Yuwen et al, 2023 ). In women with PCOS results have been inconsistent with some authors reporting higher AMH levels to be associated with better reproductive outcomes ( Xi et al, 2012 ; Tal et al, 2015 ), while others found the opposite ( Xi et al, 2012 ; Tal et al, 2020 ; Guo et al, 2021 ; Sun et al, 2021 ; Vale-Fernandes et al, 2023a ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, several studies have explored the relationship between baseline serum AMH levels and pregnancy outcomes following IVF/ICSI treatment [19][20][21]. However, in women with PCOS, results have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%